Feb 11, 2011 The transformed trigonometric functions
f(x) = a sin b(x – h) + k Recall which is which in the rule:
Match the parameters to the number: a b h k
a b h k
Which is affected by parameter a? Amplitude Period Frequency l.o.o. a = 1
Which is affected by parameter a? Amplitude Period Frequency l.o.o. a = 2
Which is affected by parameter a? Amplitude Period Frequency l.o.o. a = 3
Which is affected by parameter a? Amplitude Period Frequency l.o.o.
In fact, parameter a = amplitude Amplitude Period Frequency l.o.o.
What would be the amplitude: y = 2 cos x y = 8 sin 2x y = -3 cos x y = 4 sin 9x - 2
What would be the amplitude: y = 2 cos x y = 8 sin 2x y = -3 cos x y = 2.4 sin 9x - 2 amplitude = 2 amplitude = 8 amplitude = 3 amplitude = 2.4
What would be the value of a in the rule?
a = 5
What would be the value of a in the rule?
a = 4
What would be the value of a in the rule? a = 4
Another way to find amplitude: Amplitude = half the distance between the Max and min values = (M – m) 2 = (2 - -6) 2 = 8 2 = 4
Another way to find amplitude: Amplitude = half the distance between the Max and min values = (M – m) 2 = (2 - -6) 2 = 8 2 =
What would be the value of a in the rule?
a = 1 Amplitude = half the distance between the Max and min values = (M – m) 2 = (2 - 0) 2 = 2 2 = 1
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Amplitude =
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Amplitude = |a|
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Amplitude = |a|
Which is affected by parameter b? Amplitude Period Frequency l.o.o. b = 1
Which is affected by parameter b? Amplitude Period Frequency l.o.o. b = 2
Which is affected by parameter b? Amplitude Period Frequency l.o.o. b = 4
Which is affected by parameter b? Amplitude Period Frequency l.o.o.
Which is affected by parameter b? Amplitude Period Frequency l.o.o. 4 cycles
Which is affected by parameter b? Amplitude Period Frequency l.o.o.
In fact, b = frequency Amplitude Period Frequency = 4 = b l.o.o. y = sin 4x
What would be the frequency: y = cos 4x y = 8 sin 2x y = -3 cos (x + 1) -2 y = 2.4 sin (-9x) - 2
What would be the frequency: y = cos 4x y = 8 sin 2x y = -3 cos (x + 1) -2 y = 2.4 sin (-9x) - 2 frequency = 4 frequency = 2 frequency = frequency = 9
What would be the value of b in the rule?
b = 1
What would be the value of b in the rule?
b = 3
What would be the value of b in the rule?
b = 0.5
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Frequency =
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Frequency = |b|
And if 4 cycles have a total width of 2 then one of those cycles must have a width of... Amplitude Period Frequency l.o.o. y = sin 4x
And if 4 cycles have a total width of 2 then one of those cycles must have a width of... Amplitude Period Frequency l.o.o. y = sin 4x ?
Amplitude Period = Frequency l.o.o. y = sin 4x And if 4 cycles have a total width of 2 then one of those cycles must have a width of...
Amplitude Period = Frequency l.o.o. y = sin 4x And if 4 cycles have a total width of 2 then one of those cycles must have a width of...
Amplitude Period = Frequency l.o.o. y = sin 4x In fact, period =
Amplitude Period = Frequency l.o.o. y = sin 4x In fact, period =
What would be the period: y = cos 4x y = 8 sin 2x y = -3 cos (x + 1) -2 y = 2.4 sin (-9x) - 2 period =
What would be the period: y = cos 4x y = 8 sin 2x y = -3 cos (x + 1) -2 y = 2.4 sin (-9x) - 2 period =
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Frequency = |b| Period =
Which is affected by parameter h? Amplitude Period Frequency l.o.o. h = 0
Which is affected by parameter h? Amplitude Period Frequency l.o.o. h =.3
Which is affected by parameter h? Amplitude Period Frequency l.o.o. h =.5
Which is affected by parameter h? Amplitude Period Frequency l.o.o.
But h does shift horizontally...and this shift has a special name: Phase shift Amplitude Period Frequency l.o.o.
What would be the phase shift: y = cos 4x + 1 y = 8 sin 2(x - ) -3 y = -3 cos (x + 1) -2 y = 2.4 sin (2x + ) phase shift =
What would be the phase shift: y = cos 4x + 1 y = 8 sin 2(x - ) -3 y = -3 cos (x + 1) -2 y = 2.4 sin (2x + ) phase shift = 0 phase shift = phase shift = -1 phase shift =
What would be the value of h in the rule?
If we consider this to be a sine function, h =
What would be the value of h in the rule? If we consider this to be a sine function, h = Snake is beginning here
What would be the value of h in the rule? If we consider this to be a sine function, h = Which is /2 to the right of where it usually begins
What would be the value of h in the rule? If we consider this to be a sine function, h = In the rule, you would see:
What would be the value of h in the rule? If we consider this to be a cos function, h =
What would be the value of h in the rule? If we consider this to be a cos function, h = Tulip is beginning here
What would be the value of h in the rule? If we consider this to be a cos function, h = Which is to the right of where it usually begins
What would be the value of h in the rule? If we consider this to be a cos function, h = Which is to the right of where it usually begins
What would be the value of h in the rule? If we consider this to be a cos function, h = In the rule, you would see: (x - )
What would be the value of h in the rule?
If considered as a sine function, h =
If considered as a cos function, h =
What would be the value of h in the rule?
As a cos: h = 0
Which is affected by parameter k? Amplitude Period Frequency l.o.o. k = 0
Which is affected by parameter k? Amplitude Period Frequency l.o.o. k = 1
Which is affected by parameter k? Amplitude Period Frequency l.o.o. k = 2
Which is affected by parameter k? Amplitude Period Frequency l.o.o.
In fact, l.o.o. has equation: y = k Amplitude Period Frequency l.o.o.
What would be the l.o.o.: y = cos 4x + 1 y = 8 sin 2(x - ) - 3 y = -3 cos (x + 1) - 2 y = 2.4 sin (2x + )
What would be the l.o.o.: y = cos 4x + 1 y = 8 sin 2(x - ) - 3 y = -3 cos (x + 1) - 2 y = 2.4 sin (2x + ) l.o.o.: y = 1 l.o.o.: y = -3 l.o.o.: y = -2 l.o.o.: y = 0
What would be the value of k in the rule?
k = -1
Another way to find k: k = the number halfway between the Max and min values = (M + m) 2 = (1 + -3) 2 = -2 2 = -1
Another way to find k: k = the number halfway between the Max and min values = (M + m) 2 = (1 + -3) 2 = -2 2 = -1
What would be the value of k in the rule?
k = the number halfway between the Max and min values = (M + m) 2 = (0 + -2) 2 = -2 2 = -1
In general then: For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k l.o.o. is the line y = k
And another thing.... For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Max = k + amplitude min = k - amplitude
And another thing.... For f(x) = a sin b(x – h) + k OR: f(x) = a cos b(x – h) + k Max = k + amplitude min = k - amplitude
y = 3 sin 2x - 1
y = -1
y = 3 sin 2x - 1 y = -1
y = 3 sin 2x - 1 22
22
P = 2 /2 =
Find the rule:
y = 2 cos x
Find the rule:
y = 3 sin x
Find the rule:
y = 3 sin 2x
Find the rule:
y = 3 sin 2x - 1
Find the rule:
y = 2 sin 3(x - /4) + 1
y = 2 cos 3(x + /4) + 1
Hwk: Blog Three gizmos: –Cosine function –Sine function –Translating and scaling Sine and Cosine functions – Activity A Carousel: –p. 253 #6, 9ab, 10abd, 19 –p. 263 #6, 9, 10